The role of perceived social media agility in customer engagement / Fatin Atirah Siman - Siman, Fatin Atirah (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
The reason why we choose this article is because it is analysing the benefit of social media for users especially if it is associating with agility and customer engagement. Customer engagement in the social media is important and it can be a record for a business entity. It focuses on customer-based brand equity (CBBE) which is also important customer engagement.